2011
DOI: 10.1161/circep.110.960807
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β 1 -Mediated Fibrosis and Ion Channel Remodeling Are Key Mechanisms in Producing the Sinus Node Dysfunction Associated With SCN5A Deficiency and Aging

Abstract: Background-Mutations in the cardiac Na ϩ channel gene (SCN5A) can adversely affect electric function in the heart, but effects can be age dependent. We explored the interacting effects of Scn5a disruption and aging on the pathogenesis of sinus node dysfunction in a heterozygous Scn5a knockout (Scn5a ϩ/Ϫ ) mouse model. Methods and Results-We compared functional, histological, and molecular features in young (3 to 4 month) and old (1 year) wild type and Scn5a ϩ/Ϫ mice. Both Scn5a disruption and aging were associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 36 publications
8
88
0
1
Order By: Relevance
“…Defective FBN1 structure is associated with activa-tion of proteases in response to gradual functional tissue damage together with TGF-b-related reparative responses leading occasionally to induction of apoptosis in cells. Also, focal sclerosis create the medium for development of clinical manifestations [4]. Besides, the strategy to block TGF-b signaling ameliorated myocardial fibrosis and diastolic dysfunction in a model study [5], confirming the deteriorating effects of excessive TGF-b.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Defective FBN1 structure is associated with activa-tion of proteases in response to gradual functional tissue damage together with TGF-b-related reparative responses leading occasionally to induction of apoptosis in cells. Also, focal sclerosis create the medium for development of clinical manifestations [4]. Besides, the strategy to block TGF-b signaling ameliorated myocardial fibrosis and diastolic dysfunction in a model study [5], confirming the deteriorating effects of excessive TGF-b.…”
Section: Introductionmentioning
confidence: 73%
“…TGF-b, as shown in numerous studies, is responsible for vascular dysfunction and oxidative stress [19], myocardial fibrosis, diastolic dysfunction and other cardiovascular alterations [2,4,5]. The second possible mechanism of HRV suppression derives from the study of affected skeletal muscle function in MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis is that SCN5A-linked SND is caused by conduction block from the sinus node to the adjacent atrial myocardium, 2 while another study using SCN5A-knockout mice suggested that fibrotic changes in the sinus node are responsible for age-dependent SND. 37 We observed a lower spontaneous beating rate in D1275N-EBs than in the Controls. We should carefully extrapolate these results to in vivo systems because the EBs consisted of multiple cell types, including V-like, A-like, and N-like CMs, and because hiPSC-CMs are immature compared to adult CMs; 38 the lower spontaneous beating rate is reminiscent of bradycardia and could be due to Table S1.…”
Section: Discussionmentioning
confidence: 52%
“…Hao ve ark.nın yayınladıkları çalışmada kalpteki fibrozun sinüs nodunda disfonksiyona neden olduğu belirtilmektedir (24 (25,26). Parathormonun fibrojenik bir hormon olduğu kronik yüksekliğinin organlarda fibroza yol açtığı bilinmektedir (27).…”
Section: Gereç Ve Yöntemlerunclassified